Perceptions of workplace violence among victimized nurses: A phenomenological study in a remote island of Indonesia - Al Kautsarina , Vara; Asniar, Asniar; Kamil, Hajjul (The Journal of Palembang Nursing Studies, 2025)
Background: Workplace violence (WPV) is a serious occupational hazard that can undermine nurses’ professionalism, increase stress, and contribute to a toxic work environment. Repeated exposure to WPV is particularly concerning as it can diminish motivation, reduce job satisfaction, and negatively affect the quality of care. In hospitals located on remote small islands, where frequent interpersonal encounters are inevitable due to limited staffing and close community ties, the challenges faced by WPV-victimized nurses can be even more complex. Objective: This study aimed to explore how nurses working in a remote island hospital perceive and experience WPV Methods: A descriptive phenomenological approach was employed to capture the lived experiences of nurses at Sabang City Hospital who had experienced WPV. Participants were selected purposively. Data were collected using demographic questionnaires, semi-structured in-depth interviews, field notes, and audio recordings. The interviews explored the nature of WPV incidents, emotional and psychological impacts, and expectations for organizational support. Data were analyzed thematically to identify patterns and shared meanings. Results: Three key themes emerged: (1) perceiving WPV as a source of sadness, distress, and long-lasting trauma; (2) recognizing WPV as encompassing both verbal (insults, threats) and non-verbal (intimidation, neglect) forms; and (3) expecting more active roles from superiors and hospital management, including prevention, immediate intervention, and post-incident support. Conclusion: Nurses’ varied perceptions of WPV reflect the urgent need for structured prevention strategies and responsive management interventions. Strengthening organizational policies and support mechanisms is critical to safeguarding nurses’ well-being and fostering a safe, respectful workplace.